Estudio de factibilidad para la implementación de un centro de desarrollo comunitario para personas de la tercera edad, parroquia San Luis de Pambil, cantón Guaranda, año 2015. Quevedo. - Sisalema Bedón, Leonel Iván (2015)
The present research, it makes for the purpose of the implementation of a community development center for seniors in the parish San Luis of Pambil Canton Guaranda in the province of Bolivar. This legal research is divided into seven chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The second chapter tells everything that refers to theoretical framework, aspects: referential, conceptual and legal. In the third chapter the methodology used in the investigation described the methods used, the types of research, people, samples of techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained through surveys on the creation of a community development center for seniors in the parish San Luis of Pambil Canton Guaranda….